2008
DOI: 10.3892/ijo.32.3.701
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' tumor gene WT1-shRNA as a potent apoptosis-inducing agent for solid tumors

Abstract: Wilms' tumor gene WT1 is overexpressed in leukemia and various types of solid tumors and plays an important role in leukemogenesis and tumorigenesis. We tested apoptosis-inducing ability of short hairpin RNAs targeting exon 5 (shWTE5), exon10 (shWTE10) and 3'UTR (shWT3U) of the WT1 gene. Among the three WT1-shRNAs, since shWTE5 most effectively induced apoptosis, its ability as an apoptosis-inducing agent was intensively examined. shWTE5 induced mitochondrial damage and resultant apoptosis in five WT1-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 31 publications
4
64
1
1
Order By: Relevance
“…These results show the activation of the intrinsic apoptotic pathway by WT1 gene silencing and corroborate, in part, the report that shRNA silencing of WT1 induces apoptosis of fibrosarcoma cells. 56 WT1-1 RNAi treatment significantly increased (P ¼ 0.003) the mean survival time of tumor-bearing mice in comparison with the mice treated with WT1-2 RNAi or the untreated mice. Studies are ongoing to assess the potential of using 5% CO 2 during nebulization to increase the efficacy of aerosol delivery because it has been reported that this addition enhances transgene expression in the lung for PEI-DNA vectors.…”
Section: Discussionmentioning
confidence: 91%
“…These results show the activation of the intrinsic apoptotic pathway by WT1 gene silencing and corroborate, in part, the report that shRNA silencing of WT1 induces apoptosis of fibrosarcoma cells. 56 WT1-1 RNAi treatment significantly increased (P ¼ 0.003) the mean survival time of tumor-bearing mice in comparison with the mice treated with WT1-2 RNAi or the untreated mice. Studies are ongoing to assess the potential of using 5% CO 2 during nebulization to increase the efficacy of aerosol delivery because it has been reported that this addition enhances transgene expression in the lung for PEI-DNA vectors.…”
Section: Discussionmentioning
confidence: 91%
“…27 Inhibition of WT-1 expression by ShRNA reverses these effects, thereby eliminating leukemic cells with clonogenic potential. 28 Several studies have demonstrated that T cells specific for certain peptides of WT-1 that are expected to be immunogenic based on their predicted binding to specific HLA alleles can be generated from healthy donors and some tumor-bearing patients. [29][30][31][32] Furthermore, these T cells can lyse WT-1 ϩ tumor cells in vitro 29,30,32 and inhibit their growth in vivo in immunodeficient mice bearing human WT-1 ϩ tumor xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…15,34 Functional studies suggest that many of WT1 effects are related to particular WT1 isoforms. 8,20,[35][36][37][38][39][40] The available data on WT1 isoform expression patterns in normal and malignant hematopoiesis are scarce and the methods so far used for the detection of WT1 major isoforms (reverse transcriptase PCR, GeneScan, quantitative PCR of EX5[ þ ] and KTS[ þ ] variants) have only yielded an approximate estimation of WT1 isoform levels.…”
Section: Introductionmentioning
confidence: 99%